Role of microRNAs in the pathophysiology of addiction. (17th December 2020) - Gowen, Austin M.; Odegaard, Katherine E.; Hernandez, Jordan; Chand, Subhash; Koul, Sneh; Pendyala, Gurudutt; Yelamanchili, Sowmya V.
Abstract: Addiction is a chronic and relapsing brain disorder characterized by compulsive seeking despite adverse consequences. There are both heritable and epigenetic mechanisms underlying drug addiction. Emerging evidence suggests that non‐coding RNAs (ncRNAs) such as microRNAs (miRNAs), long non‐coding RNAs, and circular RNAs regulate synaptic plasticity and related behaviors caused by substances of abuse. These ncRNAs modify gene expression and may contribute to the behavioral phenotypes of addiction. Among the ncRNAs, the most widely researched and impactful are miRNAs. The goal in this systematic review is to provide a detailed account of recent research involving the role of miRNAs in addiction. This article is categorized under: RNA Interactions with Proteins and Other Molecules > Small Molecule‐RNA Interactions RNA in Disease and Development > RNA in Disease Abstract : Drugs of abuse impact the pathophysiology of the brain via intercellular and intracellular alterations of microRNAs. The primary glial cells of the brain, astrocytes and microglia, are responsible for inducing the majority of inflammatory cytokines that impact neurons and potentiate addiction and withdrawal symptoms. Neurons are key in forming long‐term and short‐term memories as well as conditioning through synaptic plasticity and synapto‐dendritic injury. These changes influence the majority of effects that cause the transition from recreational use to substance abuse.